Independent Curriculum Assessment: Implementation and Response From Teachers And Students At MAN 2 Pontianak - Hadi Wiyono (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
The aim of this research is to understand the implementation of the independent curriculum assessment and the evaluation of the independent curriculum from the perspective of teachers and students. Curriculum modifications bring changes to the learning and assessment system. Teachers as educators in every school tend not to adapt easily and face challenges, apart from student teachers too. This research was conducted to obtain a description of the findings in the field. Research was carried out at MA Negeri 2 Pontianak regarding the implementation of assessments that were not fully understood by teachers and were still in the process of adaptation. This research method is descriptive qualitative using observation techniques, interviews and documentation studies to obtain answers to research questions. The research sample consisted of 5 teachers and several students. The research results provide valuable insight into the extent to which the Independent Curriculum is implemented and well received by the main actors in the education process at MAN 2 Pontianak. In addition, this research also discusses its impact on students' learning experiences and teachers' teaching methods. Through this understanding, this research makes a significant contribution to understanding the development of education in Indonesia, and illustrates how schools such as MAN 2 Pontianak can adapt to curriculum changes, which aim to improve the quality of education.